2007
DOI: 10.1037/1076-898x.13.4.197
|View full text |Cite
|
Sign up to set email alerts
|

Understanding phylogenies in biology: The influence of a Gestalt perceptual principle.

Abstract: Cladograms, hierarchical diagrams depicting evolutionary histories among (groups of) species, are commonly drawn in 2 informationally equivalent formats--tree and ladder. The authors hypothesize that these formats are not computationally equivalent because the Gestalt principle of good continuation obscures the hierarchical structure of ladders. Experimental results confirmed that university students (N = 44) prefer to subdivide ladders in accordance with good continuation rather than with the underlying hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
121
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(125 citation statements)
references
References 61 publications
1
121
0
Order By: Relevance
“…Recent work has repeatedly demonstrated that detailed physical properties and relations-and the perceptual systems that process them-play an important role in reasoning using visual displays in a variety of abstract contexts including puzzles (Patsenko & Altmann, 2010), biological taxa (Novick & Catley, 2007), weather diagrams (Hegarty Canham, and Fabrikant 2010), and algebra (Kirshner, 1989). …”
Section: Introductionmentioning
confidence: 99%
“…Recent work has repeatedly demonstrated that detailed physical properties and relations-and the perceptual systems that process them-play an important role in reasoning using visual displays in a variety of abstract contexts including puzzles (Patsenko & Altmann, 2010), biological taxa (Novick & Catley, 2007), weather diagrams (Hegarty Canham, and Fabrikant 2010), and algebra (Kirshner, 1989). …”
Section: Introductionmentioning
confidence: 99%
“…Although the tree format is much more common in the professional systematics literature (see Novick and Catley 2007), the ladder format is somewhat more common in high school and college biology texts (for both nonmajors and majors at the college level; Catley and Novick 2008). This disconnect between professional and educational practice is unfortunate.…”
mentioning
confidence: 99%
“…They are usually depicted in one of two formats-tree or ladder. Previous research (Novick and Catley 2007) has found that college students have much greater difficulty understanding a cladogram's hierarchical structure when it is depicted in the ladder format. Such understanding would seem to be a prerequisite for successful tree thinking.…”
mentioning
confidence: 99%
See 2 more Smart Citations